Rab7b at the intersection of intracellular trafficking and cell migration - Distefano, Marita Borg (Commun Integr Biol, 2015)
Rab proteins are small GTPases essential for controlling and coordinating intracellular traffic. The small GTPase Rab7b regulates the retrograde transport from late endosomes toward the Trans-Golgi Network (TGN), and is important for the proper trafficking of several receptors such as Toll-like receptors (TLRs) and sorting receptors. We recently identified the actin motor protein myosin II as a new interaction partner for Rab7b, and found that Rab7b transport is dependent on myosin II. Interestingly, we also discovered that Rab7b influences the phosphorylation state of myosin II by controlling the activation status of the small GTPase RhoA. Consequently, Rab7b is important for the remodeling of actin filaments in processes such as stress fiber formation, cell adhesion, polarization and cell migration. Our finding that Rab7b can control actomyosin reorganization reveals yet another important role for Rab proteins, in addition to their already established role as master regulators of intracellular transport. Here we discuss our findings and speculate how they can explain the importance of Rab7b in dendritic cells (DCs).